Tuning oxidizing, reducing, and redox characteristics via Fe, Co, and Ni incorporation in Pd-based halloysite-supported bimetallic core–shell three-way catalysts - Yun-Ting Wang; Wei-Jing Li; Yu-Hao Lin; Ming-Yen Wey; Kui-Hao Chuang (Fuel, 2026)

A bone-homing DNA tetrahedral framework nucleic acids nanodevice orchestrates osteogenic regeneration to rescue postmenopausal osteoporosis - Qiumei Li; Fenglin Zhou; Shiyi Zeng; Yue Gao; Qian Shen; Yaping Wu; Chuan Ma; Yunfeng Lin; Jingang Xiao; Kui Huang (Chemical Engineering Journal, 2026)

Sustained-release salt reservoir enables durable solid electrolyte interphases for practical micron-sized silicon composite anodes - Kui Lin; Junke Wu; Zhengguang Song; Yuling Yi; Fuxi Peng; Shiwen Wang; Zhimin Zou; Tongbin Lan; Junxiong Wu; Chunhai Jiang (Chemical Engineering Journal, 2026)

Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

VdbHLH60-VdMYB55-VdF3'5'H module positively regulates anthocyanin biosynthesis in rabbiteye blueberry (Vaccinium ashei) fruits - Lin Deng; Luonan Shen; Kui Zhou; Chunqiong Shang; Sulin Wen; Yi Min; Yuxin Leng; Xiaopeng Wen (Plant Science, 2026)

Polyphenolic polymers for uranium decorporation with radiation protection effect - Zeru Wang; Yao Jiang; Xi Li; Linzhen Wu; Guangyuan Chen; Yawen Liu; Kui Tang; Zitong Chen; Chuanchuan Luo; Zhengguo Chen; Xiaoan Li; Lin Zhu; et al. (Journal of Hazardous Materials, 2026)

Polyacrylamide based hydrogel with high temperature and salinity tolerance: the role of aminated distilled spent grain - Xue-Li Long; Kang-Lin Chen; Hong-Ke Yang; Hong-Li Dong; Hong-Kui He; Li-Chun Dai; Zu-Guo Yang; Zhi-Xiang Xu (Biomass and Bioenergy, 2026)

A one-tube RAA-PfAgo system for rapid and sensitive detection of Monkeypox virus - Na Zhao; Xuejian Zhang; Yulu Gan; Lin Li; Yunmin Wang; Tong Xu; Yao Pan; Kui Gu; Yu Zhao (Analytica Chimica Acta, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Effects of selenium stress germination on physicochemical properties and In vitro antioxidant activity of highland barley flour - Jiayang Fu; Lin Kang; Haotian Du; Jing Hao; Xiuzhu Yu; Shuang-kui Du (Journal of Cereal Science, 2026)

Film matrix modification synergize with active ingredient introduction strategy to synthesize polysaccharide-based active packaging with enhanced barrier performance and functional activity for efficient perishable fruit preservation - Zitian Liu; Ligang Lin; Jiaxin Zhang; Kui Niu; Minglun Cheng; Yuxuan Zhu; Bin Du; Wenlong Hou; Huiyang Shang (Food Hydrocolloids, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Elucidating the effects of E-beam pre-irradiation on the Chinese safflower (Carthamus tinctorius L.): From a structure, active components, and antioxidant capacity perspective - Wenqing Zhao; Xiangrui Ren; Wei Niu; Qian Lin; Yayun Hu; Kui Li; Wenhao Li (Food Chemistry, 2026)

Lysine-directed construction of Co3O4/CeO2 interfaces for enhanced and energy-efficient catalytic styrene oxidation - Yidian Lin; Yinye Chen; Kui Niu; Jing Xu; Yuan Hu; Jiachang Zuo; Shuai Wang; Yongjin Luo; Qingrong Qian; Qinghua Chen (Chemical Engineering Journal, 2026)

Effects of prenatal exposure to hexafluoropropylene oxide dimer acid on rat and offspring mammary gland development and associated hormone levels - Lu Liu; Wendong Liu; Libing Wang; Wenjing Zhu; Dongmei Jia; Yuxin Lin; Zhugen Yang; Kui Che; Wenchao Han (Chemico-Biological Interactions, 2026)

Characteristics and driving factors of population age structure in China: A study based on the scale nesting theory - Kui Ying; Lin Ha; Liancheng Duan; Jinhong Ding (Journal of Geographical Sciences, 2026)

C-Jun NH2-terminal kinase inhibitor bentamapimod prevents RANKL-mediated osteoclastogenesis and ovariectomy-induced osteoporosis - Junming Huang; Mingchao Lin; Kui Deng; Song Zhou (In Vitro Cellular & Developmental Biology - Animal, 2026)

The Time Reliable Effect of Probiotic Clostridium butyricum on the Growth of Spotted Sea Bass (Lateolabrax maculatus) - Yiqin Deng; Liwen Xu; Keng Yang; Ziyang Lin; Shujun Zang; Kui Jiang; Wangdong Li; Nabil A. Ibrahim; Hongling Ma; Changhong Cheng; Juan Feng (Probiotics and Antimicrobial Proteins, 2026)

Resveratrol-functionalized framework nucleic acid nanoparticles enhance diabetic bone regeneration via targeted pyroptosis intervention - Chuan Ma; Long Bai; Qiumei Li; Yong Li; Fenglin Zhou; Kui Huang; Jingang Xiao; Yunfeng Lin (Chemical Engineering Journal, 2025)

Molecular dynamics simulation-driven focused virtual screening and experimental validation of Fisetin as an inhibitor of Helicobacter pylori HtrA protease - Li Gao; Xianqiong Jiang; Hongtao Duan; Yan Shen; Kui Gu; Kuilong Huang; Yuanqiang Wang; Mao Shu; Rui Zhang; Zhihua Lin (Molecular Diversity, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Influence of dual thermodynamic properties on characteristic stress and Kaiser effect of sandstone - Lin Zhang; Daoxue Yang; Kui Zhao; Yunge Zhao (Engineering Geology, 2025)

DMSPN: A distortion-mitigated network for part-level pattern parsing of underwater squids - Zhongqi Lin; Wanlin Gao; Jingdun Jia; Shenfei Pei; Kui Su; Zengwei Zheng (Computers and Electronics in Agriculture, 2025)

Hydrous and oxidised deep lithospheric mantle revealed by amphibole megacrysts from the northwest North China Craton - Lin-Lin Hu; Hong-Kun Dai; Qing Xiong; Shao-Kui Pan; Jiang-Gu Lu; Jian-Ping Zheng (Lithos, 2025)

Oily dyeing wastewater separate by PAN-EC-SiO2 EFM dual function in a single membrane separation process - Yang Hu; Yan kui Cheng; Shuang Li; Lunfeng Liu; Xiaoyan Lin (Journal of Environmental Chemical Engineering, 2025)

Linking two types of breccias to sediment-hosted stratiform copper (SSC) and iron oxide-copper-gold (IOCG) deposits in the Kangdian metallogenic belt, SW China - Xue-Qing Yin; Xin-Fu Zhao; Zhi-Kun Su; Hai-Tao Lin; Zhi-Min Zhu; Wen-Lei Song; Martin Yan Hei Li; Kui-Dong Zhao (Mineralium Deposita, 2025)

Age-stage, two-sex life table, and host plant selection behavior of the aphid Myzus persicae (Sulzer) (Hemiptera: Aphididae) on three Brassica juncea cultivars and one Brassica rapa cultivar - Mi Tian; Lin-kui Li; Zi-hua Yang (Arthropod-Plant Interactions, 2025)

Reversing N-intermediate adsorption configuration over Mo Fe diatomic sites enables enhanced nitrate reduction - Kui Wang; Junru Li; Xinru Wei; Zhiqiang Zhao; Xianbin Meng; Kai Li; Yuzheng Cui; Junjie Mao; Baotao Kang; Yuqing Lin (Chemical Engineering Journal, 2025)

Evaluation and Dissection of Sensory Quality Traits for Potato Taste - Ying Wang; Wan-lin Yang; Fan-kui Zeng; Chun-ni Lei; Qiong-fen Yang; Jian Wang (Potato Research, 2025)
The sensory qualities of potatoes significantly influence consumer preference. This study evaluated the sensory qualities of 66 potato varieties, focusing on representatives of distinct taste types for detailed analysis: sensory evaluation, taste, nutritional components, texture properties, physicochemical characteristics of starch, and volatile aroma compounds. Sensory evaluation of these potato varieties identified the landrace “Kaihua Yangyu” as the most favoured by consumers. The favourable taste of Kai Hua Yang Yu was attributed to (1) soft, dry, and non-sticky texture; (2) starch with higher peak viscosity, easier gelatinisation (below 70 ℃), higher setback value (2776 RVU), and larger granule size (41.63 ± 9.90 μm) compared with other such as YS105 and Cooperation88; and (3) distinctive umami flavour, a trait notably associated with elevated levels of aspartic acid and glutamic acid.

Low temperature hydrochar from sewage sludge enhancing polyacrylamide-based preformed particle gels with high temperature and salinity tolerance - Bei-Bei Wu; Yan-Yan Xu; Fan Gao; Ya-Jun Wu; Lin-Hui Xi; Zhi Kang; Hong-Kui He; Zu-Guo Yang; Zhi-Xiang Xu (Journal of Water Process Engineering, 2025)

An innovative adaptive double-skin wall system integrating a phase change material layer: comprehensive performances across different climate zones for heating - Shiqiang Zhou; Kui Shan; Qingshan Lin; Xiaoxi Guo; Mengjie Song; Long Zhang (Building and Environment, 2025)

Construction of a molecularly imprinted electroluminescence sensor for pyrimethanil detection via dummy template imprinting combined with click-chemical labeling of mimic enzymes - Lijuan Lin; Peng Gao; Minjin Wu; Kui Luo; Jianping Li (Analytica Chimica Acta, 2025)

Steroidal saponins and homoisoflavonoids from the fibrous roots of ophiopogon japonicus and their anti-pulmonary fibrosis activities - Hang-Yi Pu; Yu Cao; Xi-Lang Jiang; Lin-Han Yang; Ming-Kui Wang; Fei Wang; Lun Wang (Natural Product Research, 2025)

Differential microbial degradation of cross-linked Polythene by Aspergillus niger in space and on the ground - Shuyuan Zhang; Lei Dang; Weiliang Li; Qin Zhang; Kui Xiao; Tong Tong; Qianqian Liu; Lingling Ma; Nana Chen; Lantao Zhang; Yali Feng; Yan Song; et al. (Chemical Engineering Journal, 2025)

Metabolomic and transcriptomic analyses provide insights into temperature and light regulated anthocyanin accumulation in flesh of ‘Furongli’ plum (Prunus salicina Lindl.) - Zhizhen Fang; Kui Lin-Wang; Yanjuan Lin; Richard V. Espley (Postharvest Biology and Technology, 2025)

Functionality of the MYB1 Transcription Factor in the Transactivation of Leucoanthocyanidin Reductase (LAR) Promoters of Fragaria × Ananassa and Fragaria Chiloensis - Claudia Gómez-Parada; Carlos R. Figueroa; Kui Lin-Wang; Alejandra Moya-León; Richard V. Espley; Andrew C. Allan; Raul Herrera (Journal of Plant Growth Regulation, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Light-emitting diodes affect plantlet growth of Spathiphyllum cannifolium by regulating photosynthesis and sucrose metabolism during ex vitro rooting - Shuo Yu; Kui-Hua Li; Hang-Lin Song; Yue Dai; Yin-Ji Jiang; Mei-Yu Jin; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Modeling of wave-induced drift based on stepwise parameter calibration - Kui Zhu; Xueyao Chen; Lin Mu; Dingfeng Yu; Runze Yu; Zhaolong Sun; Tong Zhou (Frontiers in Marine Science, 2025)
The motion of waves in water causes the slow movement of drifting sea targets—a phenomenon usually ignored in target-drift prediction models for maritime search and rescue (SAR). This study examined the wave-induced drift’s influence on field-observation experiments involving two common, differently sized SAR targets—an offshore fishing vessel (OFV) and a person in the water (PIW)—using parameter stepwise calibration and machine-learning (ML) methods. The sample of wave-induced drift velocity was obtained by gradually separating current-induced (CI) drift’s and wind-induced (WI) drift’s influence from the target-drift velocity using the least-square method and AP98 model. A force analysis method and three ML methods, long short-term memory (LSTM), back-propagation (BP) neural network, and random forest (RF), were used to fit the wave-induced drift velocity by combining eight different parameter schemes. Finally, the drift trajectories considering the influence of waves were fitted and verified based on 2 independent samples respectively. Compared with the force analysis method, the accuracy of the ML methods in the verification test was higher. In addition, the results show that for OFVs, considering wave-induced drift’s influence in the ensemble-trajectory prediction could improve the simulation accuracy. However, for a PIW, no significant improvement was observed. This result also indicates that wave-induced drift may not be simply ignored in large SAR targets’ drift prediction.

Targeting bacterial phospholipids and their synthesis pathways for antibiotic discovery - Meirong Song; Shang Chen; Wenhan Lin; Kui Zhu (Progress in Lipid Research, 2024)

Bridging the Gap: Establishing Spatial Correlations and Type Conversion Relationships among Different Aerosol Idetification Methods - Qi-Xiang Chen; Chun-Lin Huang; Shi-Kui Dong; Kai-Feng Lin (Atmospheric Research, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Efficient removal of perrhenate/pertechnetate by a pyridinium-based porous polymer - Miaomiao He; Yuxuan Chen; Guangyuan Chen; Wenhao Li; Mingxing Zhang; Chao Zhang; Hao Zhang; Xingyi Long; Kui Tang; Tao Duan; Lin Zhu (Environmental Pollution, 2024)

Cu-based bubble and ion sieve for ampere-level hydrogen evolution - Si-Wei Yan; Chuan-Qi Cheng; Fei-Fei Zhang; Ze-Yu Zhang; Kui Lin; Peng-Fei Yin; Rui Zhang; Jing Yang; Cun-Ku Dong; Jing Mao; Hui Liu; Xi-Wen Du (Chemical Engineering Journal, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Study on biodegradation of polyurethane coating on PCB by Aspergillus brasiliensis in space - Qianqian Liu; Wende Zhang; Junxia Yuan; Nana Chen; Qin Zhang; Yali Feng; Jinlu Yang; Lin Lu; Xunfeng Zhao; Chaofang Dong; Hong Yin; Kui Xiao (Chemical Engineering Journal, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Tumor microenvironment responsive multifunctional smart living materials based on engineered bacteria for inducing macrophage polarization to enhance tumor immunotherapy - Ning Jiang; Kui Zhao; Chengcheng Liu; Xiaojuan Zhu; Xumeng Huang; Lin Yang; Xiaoping Yi; Yingping Zhuang; Bangce Ye; Jiangchao Qian; Jiaofang Huang (Chemical Engineering Journal, 2024)

Multi-object detection and behavior tracking of sea cucumbers with skin ulceration syndrome based on deep learning - Fengli Ge; Kui Xuan; Peng Lou; Juan Li; Lingxu Jiang; Jiasheng Wang; Qi Lin (Frontiers in Marine Science, 2024)
Skin ulceration syndrome of sea cucumbers is one of the most serious diseases in intensive aquaculture, and it is the most effective way of preventing the spread of this disease to detect the abnormal behavior of sea cucumbers in time and take corresponding measures. However, the detection and tracking of multi-object is a hard problem in sea cucumber behavior analysis. To solve this problem, this paper first proposes a novel one-stage algorithm SUS-YOLOv5 for multi-object detection and tracking of sea cucumbers. The proposed SUS-YOLOv5 optimizes the maximum suppression algorithm in the overlapping region of the object detection box. Next, the SE-BiFPN feature fusion structure is proposed to enhance the transmission efficiency of feature information between deep and shallow layers of the network. Then, a MO-Tracking algorithm is proposed integrated with DeepSORT to achieve real-time multi-object tracking. Experimental results show that the mAP @0.5 and mAP @0.5:0.95 of the proposed object detector reach 95.40% and 83.80%, respectively, which are 3.30% and 4.10% higher than the original YOLOv5s. Compared with the traditional SSD, YOLOv3, and YOLOv4, the mAP of SUS-YOLOv5 is improved by 5.49%, 1.57%, and 3.76%, respectively. This research can realize the multi-object detection and tracking, which lays the foundation for the prediction of skin ulceration syndrome in sea cucumbers and has a certain practical application value for improving the intelligence level of aquaculture.

Impacts of the aerosol mixing state and new particle formation on CCN in summer at the summit of Mount Tai (1534m) in Central East China - Zihao Wu; Honglei Wang; Yan Yin; Lijuan Shen; Kui Chen; Jinghua Chen; Zhongxiu Zhen; Yi Cui; Yue Ke; Sihan Liu; Tianliang Zhao; Wen Lin (Science of The Total Environment, 2024)

Artificial humic acid coated ferrihydrite strengthens the adsorption of phosphate and increases soil phosphate retention - Shuang Gai; Bing Liu; Yibo Lan; Lin Han; Yixiong Hu; Guanghao Dongye; Kui Cheng; Zhuqing Liu; Fan Yang (Science of The Total Environment, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Analyzing the correlation between quinolone-resistant Escherichia coli resistance rates and climate factors: A comprehensive analysis across 31 Chinese provinces - Yi-Chang Zhao; Zhi-Hua Sun; Ming-Xuan Xiao; Jia-Kai Li; Huai-yuan Liu; Hua-Lin Cai; Wei Cao; Yu Feng; Bi-Kui Zhang; Miao Yan (Environmental Research, 2024)

A clean process for liquid-phase synthesis of α-PbO based on the selective leaching of lead sulfate from spent lead paste - Zhangqing Chen; Kui Huang; Guoliang Huang; Xinke Shan; Lin Wei; Haili Dong; Jujun Ruan (Journal of Environmental Chemical Engineering, 2024)

GPIC: A set of high-efficiency CUDA Fortran code using gpu for particle-in-cell simulation in space physics - Qiyang Xiong; Shiyong Huang; Zhigang Yuan; Bharatkumar Sharma; Lvlin Kuang; Kui Jiang; Lin Yu (Computer Physics Communications, 2024)

Investigations in mutation breeding and culturing media by Xanthophyllomyces dendrorhous - Qibin Lin; Xiaoru Wang; Liang Zhang; Yingyu Shu; Yurou Zhang; Ruoting Zhan; Kui Wang (Biocatalysis and Agricultural Biotechnology, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Activate the filtration capability of 3.5 nm ultra-large pores and eliminate the requirement of pore homogeneity for carbon nanotube array membranes - Na Li; Zemeng Feng; Yiyue He; Zhaogang Peng; Xiangrui Meng; Huijuan Lin; Kui Xu (Desalination, 2024)

Cyclic Impact Damage and Water Saturation Effects on Mechanical Properties and Kaiser Effect of Red Sandstone Under Uniaxial Cyclic Loading and Unloading Compression - Kui Zhao; Lin Zhang; Daoxue Yang; Jiefang Jin; Peng Zeng; Xing Wang; Shanhu Ran; Dongming Deng (Rock Mechanics and Rock Engineering, 2024)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

Correction to: Myeloid‑specific deletion of chitinase‑3‑like 1 protein ameliorates murine diet‑induced steatohepatitis progression - Andrea D. Kim; Lin Kui; Benedikt Kaufmann; Sung Eun Kim; Aleksandra Leszczynska; Ariel E. Feldstein (Journal of Molecular Medicine, 2023)

Relationships between nitrogen-specific genes and soil potentials are more complex than single linear ones - Yanfen Wang; Shutong Zhou; Biao Zhang; Jianqing Du; Anquan Xia; Lin Chen; Li Tang; Kui Wang; Wenjing Liu; Zongsong Wang; Lizhen Cui; Kai Xue (Applied Soil Ecology, 2023)

Spatial symmetry and contrasting controls of surface pH and aragonite saturation state in the western North Pacific - Cheng-long Li; Yingxu Wu; Kui Chen; Hongmei Lin; Liqi Chen; Di Qi (Frontiers in Marine Science, 2023)
Oceanic uptake of anthropogenic CO 2 causes a decrease in seawater pH and aragonite saturation state (Ω arag ), a process known as ocean acidification (OA). The western North Pacific is a hotspot for anthropogenic CO 2 sinks; however, the spatiotemporal variability of pH and Ω arag and their controlling mechanisms remain unexplored. In this study, we provide high-frequency and high-precision underway measurements of sea surface p CO 2 and pH to investigate the distribution and drivers of OA metrics across different hydrochemical gradients in the western North Pacific in late spring 2018, a season with the highest primary production in the year. Our results show that the surface pH reached near air-sea equilibrium in the subtropical zone but gradually increased northward across the Kuroshio Recirculation (KR) zone and peaked in the Kuroshio Extension (KE) zone. We found that sea surface temperature played the most prominent role in regulating pH, which was also counteracted by the effects of air–sea gas exchange and vertical mixing. In contrast, the distribution of Ω arag largely mirrored the pH and was governed by air–sea gas exchange and vertical mixing, the effects of which on Ω arag were enhanced by temperature. Biological activity thrived in the KE zone to increase both pH and Ω arag , which further reinforced the latitudinal pattern of pH, but weakened that of Ω arag . These findings are based on direct in situ measurements of pH and improve our understanding of the spatiotemporal variability of OA metrics in the western North Pacific region.

The Dof transcription factor COG1 acts as a key regulator of plant biomass by promoting photosynthesis and starch accumulation - Zhuoyun Wei; Haoyong Zhang; Meng Fang; Shuyuan Lin; Mingsong Zhu; Yuxiu Li; Limin Jiang; Tianliang Cui; Yanwei Cui; Hong Kui; Liang Peng; Xiaoping Gou; et al. (Molecular Plant, 2023)

Fertile mantle domains with different metasomatic features beneath the eastern North China Craton: Transformation from variably auto-metasomatized asthenospheric upwelling - Lei-Tao Cao; Jian-Ping Zheng; Hong-Kun Dai; Qing Xiong; A-Bing Lin; Shao-Kui Pan (Lithos, 2023)

Biogeographic distribution patterns of the bacterial and archaeal communities in two seamounts in the Pacific Ocean - Ning-Hua Liu; Jun Ma; Si-Qi Lin; Kui-Dong Xu; Yu-Zhong Zhang; Qi-Long Qin; Xi-Ying Zhang (Frontiers in Marine Science, 2023)
Seamounts are important components of seafloor topography and have a significant influence on the biogeographic distribution of marine microorganisms. However, current studies on the biogeographic distribution patterns of microorganisms in the ocean around seamounts are still inadequate. This study investigated the bacterial and archaeal communities present in the water column at various depths around the Kocebu and M5 seamounts located in the western Pacific Ocean using 16S rRNA gene high-throughput sequencing. The analyses showed that microbial communities had different alpha diversities and species compositions in samples from the same depth, and disruption of vertical stratification of microbes was observed in deep water layers at both seamounts. The stochastic processes dominated the microbial community assembly around two seamounts, for the Kocebu Seamount, drift accounted for 34.99% and 64.85% in the bacterial and archaeal community assembly processes, respectively; while the corresponding values for the M5 Seamount were 14.07% and 58.65%. Despite the low explanatory power of environmental variables for microbial communities, dissolved inorganic nitrogen was the most significant factor influencing the microbial community structure in seawater around seamounts. Overall, our results revealed that the presence of Kocebu and M5 seamounts enhance the vertical mixing of microbial communities in the surrounding seawater, and stochastic processes dominate microbial community assembly. Considering the numerous seamounts in the global ocean, the impacts of seamounts on marine ecosystems and biogeochemical cycles may have been underestimated.

Probabilistic modelling of surface drift prediction in marine disasters based on the NN–GA and ARMA model - Kui Zhu; Lin Mu; Runze Yu; Xiaoyu Xia; Haiwen Tu (Ocean Engineering, 2023)

A green yttrium extraction system containing naphthenic acid, trioctyl/decylamine and isopropanol - Kui Liu; Zengkai Wang; Jing Mei; Baibai Lu; Yao Wu; Shenglong Yang; Xijie Lin (Journal of Cleaner Production, 2023)

Solidification/stabilisation behaviours of Zn2+ in magnesium potassium phosphate cement: Experiments and density functional theory study - Renjie Mi; Zhibin Zhang; Weiming Ji; Shichang Liu; M.F. Kai; Kui lin; Yongshan Tan (Environmental Research, 2023)

A callus-derived regeneration and Agrobacterium-mediated gene transformation developed for bilberry, Vaccinium myrtillus - Yanping Song; Wenbo Luo; Ying Wu; Xiaojie Li; Nick W. Albert; Yinhai Zhang; Xiangtao Chen; Kui Lin-Wang; Cecilia H. Deng; Zhubing Hu; Bingsong Zheng; Xiaofei Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Myeloid-specific deletion of chitinase-3-like 1 protein ameliorates murine diet-induced steatohepatitis progression - Andrea D. Kim; Lin Kui; Benedikt Kaufmann; Sung Eun Kim; Aleksandra Leszczynska; Ariel E. Feldstein (Journal of Molecular Medicine, 2023)
Chitinase-3-like 1 protein (CHI3L1) is a secreted glycoprotein, strongly correlated with fibrosis severity in chronic liver diseases including non-alcoholic steatohepatitis (NASH). However, the mechanisms by which CHI3L1 contributes to fibrogenesis remain undefined. Here, we showed that infiltrating monocyte-derived liver macrophages represent the main source of CHI3L1 in murine NASH. We developed a floxed CHI3L1 knock-out (KO) mouse to further study the cell-specific role of CHI3L1 ablation. Wildtype (WT) and myeloid cell-specific CHI3L1 KO mice (Cre Lyz ) were challenged with a highly inflammatory and fibrotic dietary model of NASH by administering choline-deficient high-fat diet for 10 weeks. Macrophage accumulation and inflammatory cell recruitment were significantly ameliorated in the Cre Lyz group compared to WT (F4/80 IHC p < 0.0001, CD11b IHC p < 0.0001). Additionally, hepatic stellate cell (HSC) activation and fibrosis were strongly decreased in this group (α-SMA IHC p < 0.0001, picrosirius red staining p < 0.0001). In vitro studies were performed stimulating bone marrow derived macrophages, THP-1 (human monocytes) and LX2 (human HSCs) cells with recombinant CHI3L1 to dissect its relationship with fibrosis development. Results showed an important role of CHI3L1 regulating fibrosis-promoting factors by macrophages ( TGFB1 p < 0.05, CTGF p < 0.01) while directly activating HSCs ( ACTA2 p < 0.01, COL1A1 p < 0.01), involving IL13Rα2 as the potential mediator. Our findings uncovered a novel role of CHI3L1 derived from liver macrophages in NASH progression and identifies this protein as a potential anti-fibrotic therapeutic target. Key messages We showed that CHI3L1 expression is increased in murine CDAA-HFAT diet NASH model, and that infiltrating macrophages are a key source of CHI3L1 production. Myeloid cell-specific CreLyz CHI3L1 knock-out in mice fed with CDAA-HFAT diet improved the NASH phenotype, with significantly reduced accumulation of pro-inflammatory macrophages and neutrophils compared with WT group. DEG and qPCR analysis of genes in CreLyz CHI3L1 knock-out mouse liver showed the mechanistic role of CHI3L1 in cellular chemotaxis. HSC is directly activated by CHI3L1 via receptor IL13Rα2, leading to upregulation of collagen deposition and pro-fibrotic gene, TIMP-1 and TIMP-2 release in whole liver. Direct stimulation of macrophages with CHI3L1 leads to upregulated expression of HSC-activation factors, suggesting its role in modulating macrophage-HSC crosstalk.

Geographical variation in community‐wide herbivory matches patterns of intraspecific variation instead of species turnover - Xiang Liu; Ziyuan Lin; Kui Hu; Xingxing Wang; Peng Zhang; Yao Xiao; Li Zhang; Mu Liu (Global Ecology and Biogeography, 2023)
Aim Attempts over the past 30 years to explain geographical variation in the strength of herbivore pressure have given rise to ecological hypotheses like the latitudinal herbivory hypothesis. This hypothesis, however, has rarely been tested using community‐level data. Therefore, the aim of our study was to examine the patterns and potential mechanisms underlying geographical variation in community‐wide herbivory. Location The Qinghai‐Tibetan Plateau. Time Period July 2021. Major Taxa Studied Plants. Methods We selected 43 grassland sites along a 1500‐km latitudinal gradient ( c . 27°N to 39°N) and a 2698‐m elevational gradient (1886–4584 m) on the Qinghai‐Tibetan Plateau. We evaluated geographical patterns in invertebrate herbivory pressure at the population and community levels, while also evaluating the importance of geographical variation in mediating the effects of abiotic and biotic factors on intraspecific variation (through changes in herbivory on component species) and species turnover effects (through changes in plant community composition). Results Community‐wide herbivory decreased with latitude, mirroring intraspecific variation, while species turnover effects did not vary along any tested geographical gradients. Furthermore, we found that geographical variation in community‐wide herbivory was strongly positively correlated with soil nitrogen content. We also found a positive effect of soil nitrogen content on intraspecific variation and a negative effect of plant community biomass on species turnover effects. Main Conclusions The latitudinal gradient in community‐wide herbivory was primarily mediated by intraspecific variation, which was in turn associated with a gradient in soil nitrogen content. Our findings highlight the need for community‐wide assessments of geographical variation in plant–herbivore interactions, decomposing community‐wide herbivory into intraspecific variation and species turnover effects.

Epitomizing biohydrogen production from microbes: Critical challenges vs opportunities - Jia Min Woon; Kuan Shiong Khoo; Asla A. AL-Zahrani; Meznah M. Alanazi; Jun Wei Lim; Chin Kui Cheng; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sun Yi-Ming; Kuen-Song Lin; John Chi-Wei Lan; Md Sohrab Hossain; et al. (Environmental Research, 2023)

Investigation of physical and mechanical properties of clay soils around deep shafts - Yuansheng Lin; Zhen Huang; Zhenquan Jiang; Cong Gong; Kui Zhao; Qixiong Gu; Yufan Wu; Rui Zhang; Jiabo Geng (Bulletin of Engineering Geology and the Environment, 2023)

Discovery of uncommon terpenoids from the South China Sea soft coral Sinularia scabra - Kui Wang; Jing Liu; Jian Huang; Xue Leng; Te Li; Han Ouyang; Wenhan Lin; Xia Yan; Shan He (Phytochemistry, 2023)

Engineering triple internal electric fields in Ag NWs@BaTiO3 composites for ultrasonic-visible-light driven antibacterial activity - Guoqiang Shu; Yaqi Lin; Rui Zhong; Xiaofan Su; Shanhong Guo; Chao Wang; Changan Zhou; Lei Song; Li Xie; Kui Ma; Hairong Yue (Chemical Engineering Journal, 2023)

Studies on the interaction of five triazole fungicides with human renal transporters in cells - Jing Nie; Jiabei Zhou; Yi Shen; Ruimiao Lin; Haihong Hu; Kui Zeng; Huichang Bi; Min Huang; Lushan Yu; Su Zeng; Jing Miao (Toxicology in Vitro, 2023)

The contribution of subliminal perceptions, dietary habits, and psychological traits to the perception of oral tingling and burning sensations - Lu-lu Zhang; Chao Ma; Hou-yin Wang; Ying-ming Zheng; Qing-bin Zhang; Kui Zhong; Bo-lin Shi; Lei Zhao (Food Research International, 2023)

Identification and Characterization of Bacillus subtilis B9: A Diazotrophic Plant Growth-Promoting Endophytic Bacterium Isolated from Sugarcane Root - Yi-ning Di; Ling Kui; Pratiksha Singh; Lu-feng Liu; Lin-yan Xie; Li-lian He; Fu-sheng Li (Journal of Plant Growth Regulation, 2023)
Plant endophytic microorganisms, which can enhance plant growth and resistance to biotic and abiotic stresses, are untapped resources with large potential applications for crop production. However, the endophytic community is influenced by multiple factors, such as host genetics, the environment, and other microbes. Thus, it is important to characterize well-adapted endophytes from native crops. We isolated 43 endophytic bacteria from sugarcane cultivar Yunzhe-99-91. All these 43 isolates were examined in vitro for nitrogenase activity and the ability to dissolve phosphorus and produce siderophore. One of these strains, B9, identified as Bacillus subtilis and showed maximum plant growth promotion, was selected for detailed studies. B9 promoted the production of organic acids such as propionic acid, acetic acid, malic acid and citric acid, and the production of phytohormones, including indole-3-acetic acid, cytokinin, 6-benzyladenine, and zeatin. Moreover, B9 significantly promoted the growth of sugarcane plantlets and increased the content of nitrogen, phosphorus, and potassium in the seedlings by 29.26%, 50.78%, and 15.49%, respectively. The photosynthetic rate, root development, and chlorophyll content were also improved with varying degrees compared to the non-inoculated control. The cotyledon and hypocotyl of sugarcane gems germinated faster when co-cultured with the B9 strain compared with control group. Colonization assay showed that B9 was mainly colonized in the roots, followed by the stems and leaves. In conclusion, the positive interaction between endophytic strain B9 and sugarcane may provide long-lasting benefits and a direction for developing and utilizing B9 as a biofertilizer for sugarcane cultivation to decrease fertilizer application.

Spatial scale‐dependent dilution effects of biodiversity on plant diseases in grasslands - Xiang Liu; Yao Xiao; Ziyuan Lin; Xingxing Wang; Kui Hu; Mu Liu; Yimin Zhao; Yanwen Qi; Shurong Zhou (Ecology, 2023)
The rapid biodiversity losses of the Anthropocene have motivated ecologists to understand how biodiversity affects infectious diseases. Spatial scale is thought to moderate negative biodiversity–disease relationships (i.e., dilution effects) in zoonotic diseases, whereas evidence from plant communities for an effect of scale remains limited, especially at local scales where the mechanisms (e.g., encounter reduction) underlying dilution effects actually work. Here, we tested how spatial scale affects the direction and magnitude of biodiversity–disease relationships. We utilized a 10‐year‐old nitrogen addition experiment in a Tibetan alpine meadow, with 0, 5, 10, and 15 g/m 2 nitrogen addition treatments. Within the treatment plots, we arranged a total of 216 quadrats (of either 0.125 × 0.125 m, 0.25 × 0.25 m or 0.5 × 0.5 m size) to test how the sample area affects the relationship between plant species richness and foliar fungal disease severity. We found that the dilution effects were stronger in the 0.125 × 0.125 m and 0.25 × 0.25 m quadrats, compared with 0.5 × 0.5 m quadrats. There was a significant interaction between species richness and nitrogen addition in the 0.125 × 0.125 m and 0.25 × 0.25 m quadrats, indicating that a dilution effect was more easily observed under higher levels of nitrogen addition. Based on multigroup structural equation models, we found that even accounting for the direct impact of nitrogen addition (i.e., “nitrogen‐disease hypothesis”), the dilution effect still worked at the 0.125 × 0.125 m scale. Overall, these findings suggest that spatial scale directly determines the occurrence of dilution effects, and can partly explain the observed variation in biodiversity–disease relationships in grasslands. Next‐generation frameworks for predicting infectious diseases under rapid biodiversity loss scenarios need to incorporate spatial information.

Assessment of factors affecting the diurnal variations of atmospheric PAHs based on a numerical simulation - Zhongxiu Zhen; Yan Yin; Haowen Zhang; Jingyi Li; Jianlin Hu; Lin Li; Xiang Kuang; Kui Chen; Honglei Wang; Qingyuan Yu; Xin Zhang (Science of The Total Environment, 2023)

DNA methylation reprogramming provides insights into light-induced anthocyanin biosynthesis in red pear - Hai-Nan Liu; Qun Shu; Kui Lin-Wang; Richard V. Espley; Andrew C. Allan; Mao-Song Pei; Xiao-Long Li; Jun Su; Jun Wu (Plant Science, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Research on Spatial Kinematics and Cutting Load Characteristics of TBM Disc Cutters - Kui Zhang; Yulin Zhang; Jie Liu; Laikuang Lin; Xuejun Zheng (Geotechnical and Geological Engineering, 2023)

Determining the drift characteristics of open lifeboats based on large-scale drift experiments - Haiwen Tu; Lin Mu; Kai Xia; Xiaodi Wang; Kui Zhu (Frontiers in Marine Science, 2022)
Lifeboat is one of the most important life-saving equipment for escaping at sea when a ship is abandoned in an extreme emergency. An accurate drift model can help rescuers find the drift position of lifeboat in the shortest time, thus improving the efficiency of marine search and rescue (SAR) at sea and ensuring the safety of wrecked people. The purpose of this paper is to investigate the drift characteristics and to develop an accurate drift prediction model for the open lifeboat. First, large-scale drift experiments were conducted to analyze the drift characteristics with three 6.5-meter-long real-size open lifeboats in the South China Sea. Next, three drift prediction models of the lifeboats were developed using the least squares method based on the drift experimental data. Finally, the drift prediction models of the lifeboats were compared and evaluated using the Lagrangian method and Monte Carlo technique, respectively. Results indicate that the probability of positive crosswind leeway (CWL) of the open lifeboat is 47.5%. The jibing frequency is 6% per hour, and the maximum leeway divergence angle is 45°. These drift characteristics are very important for the prediction of the open lifeboat drift trajectory. The comparison results of three drift models show that the improved drift model is more accurate than the other two drift models for predicting drift trajectories of the open lifeboat, which can be directly applied to maritime search and rescue operations in the South China Sea.

Release of Endogenous Brain-derived Neurotrophic Factor into the Lateral Entorhinal Cortex from the Paraventricular Thalamus Ameliorates Social Memory Deficits in a Mouse Model of Alzheimer’s Disease - Yun-Long Xu; Lin Zhu; Zi-Jun Chen; Xiao-Fei Deng; Pei-Dong Liu; Shan Li; Bing-Chun Lin; Chuan-Zhong Yang; Wei Xu; Kui-Kui Zhou; Ying-Jie Zhu (Neuroscience Bulletin, 2022)

Vector angle grouping-based solution separation for multipath/NLOS detection and exclusion with the enhancement of doppler test - Jin Chang; Xingqun Zhan; Yawei Zhai; Shizhuang Wang; Kui Lin; Rong Yang (GPS Solutions, 2022)

Endothelial cells induce degradation of ECM through enhanced secretion of MMP14 carried on extracellular vesicles in venous malformation - Gao-Hong Chen; Jie-Gang Yang; Hou-Fu Xia; Lin-Zhou Zhang; Yin-Hsueh Chen; Kui-Ming Wang; Xu Duan; Lian-Zhi Wu; Yi-Fang Zhao; Gang Chen (Cell and Tissue Research, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

EV-T synergizes with AZD5582 to overcome TRAIL resistance through concomitant suppression of cFLIP, MCL-1, and IAPs in hepatocarcinoma - Kui Su; Qian Yuan; Huan Hou; Changhong Ke; Chaohong Huang; Shuyi Li; Jianwu Sun; Xin Yuan; Yue Lin; Yiqing Chen; Huijuan Xin; Xiaoping Liang; et al. (Journal of Molecular Medicine, 2022)

The role of social networks in relocation induced by climate-related hazards: an empirical investigation in China - Jing Tan; Kui Zhou; Li Peng; Lei Lin (Climate and Development, 2022)

Rapid visual genotyping method for germline mutants with small genomic fragment deletion by allele-specific PCR and lateral flow nucleic acid biosensor - Qiuju Su; Xiang Zhou; Tianwen Wu; Kui Li; Wentao Xu; Zhenyu Lin; Ping Shen; Bang Liu (Molecular Biology Reports, 2021)

Nanoselenium and Selenium Yeast Have Minimal Differences on Egg Production and Se Deposition in Laying Hens - Tian-Tian Meng; Xue Lin; Chun-Yan Xie; Jian-Hua He; Yang-Kui Xiang; Yi-Qiang Huang; Xin Wu (Biological Trace Element Research, 2021)

Comparison of the effects of deep and moderate neuromuscular block on respiratory system compliance and surgical space conditions during robot-assisted laparoscopic radical prostatectomy: a randomized clinical study - Shao-jun Zhu; Xiao-lin Zhang; Qing Xie; Yan-feng Zhou; Kui-rong Wang (Journal of Zhejiang University-SCIENCE B, 2020)

Fermented dairy foods intake and risk of cardiovascular diseases: A meta-analysis of cohort studies - Kui Zhang; Xiaogang Chen; Lin Zhang; Zhenhua Deng (Critical Reviews in Food Science and Nutrition, 2020)

Molecular characterization of the Krüppel-homolog 1 and its role in ovarian development in Sogatella furcifera (Hemiptera: Delphacidae) - Kui Hu; Ping Tian; Lu Yang; Yan Tang; Lin Qiu; Hualiang He; Wenbing Ding; Youzhi Li (Molecular Biology Reports, 2020)

Evaluation of the impact of karst depression-type impoundments on the underlying karst water systems in the Gejiu mining district, southern Yunnan, China - Hai-Yan Gao; Ze-Min Xu; Kun Wang; Zhe Ren; Kui Yang; Yong-Jun Tang; Lin Tian; Ji-Pu Chen (Bulletin of Engineering Geology and the Environment, 2019)

Evaluation of reference genes and expression of key genes involved in the isoprenoid metabolic pathway of rice leaves after infection by the Southern rice black-streaked dwarf virus - Kui Hu; Lin Qiu; Wenbing Ding; Hualiang He; Youzhi Li (Molecular Biology Reports, 2019)

Rainfall difference between the deposition fan and source area of Touzhai Landslide in Yunnan, China - Kun Wang; Zhe Ren; Xuefeng Mei; Lin Tian; Kui Yang; Zhenhua Zhou; Jianjie Luo; Zemin Xu (Bulletin of Engineering Geology and the Environment, 2019)

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

A new triterpene diglycoside from the roots of Bupleurum chinense DC. and its inhibitory effect on adipogensis in 3T3-L1 cells - Yujing Feng; Zhou-Wei Wu; Yanyan Luo; Liang Chen; Yufeng Cao; Lun Wang; Aftab Yaseen; Bin Chen; Ashfaq Ahmad Khan; Ming-Kui Wang; Guo-Lin Zhang; Xin-Feng Wang; et al. (Medicinal Chemistry Research, 2019)

A refined model for lithosphere evolution beneath the decratonized northeastern North China Craton - A-Bing Lin; Jian-Ping Zheng; Qing Xiong; Sonja Aulbach; Jiang-Gu Lu; Shao-Kui Pan; Hong-Kun Dai; Hui Zhang (Contributions to Mineralogy and Petrology, 2019)

Identification of Genes Involved in Flavonoid Biosynthesis of Chinese Narcissus (Narcissus tazetta L. var. chinensis) - Guiqing Wang; Biyun Yang; Jiacheng Wu; Peng Luo; Muhammad Anwar; Andrew C. Allan; Kui Lin-Wang; Richard V. Espley; Lihui Zeng (Plant Molecular Biology Reporter, 2018)

Impacts of small woody debris on slurrying, persistence, and propagation in a low-gradient channel of the Dongyuege debris flow in Nu River, Southwest China - Yong-Jun Tang; Ze-Min Xu; Tai-Qiang Yang; Zhen-Hua Zhou; Kun Wang; Zhe Ren; Kui Yang; Lin Tian (Landslides, 2018)

Taraxasterol suppresses the growth of human liver cancer by upregulating Hint1 expression - Tianhao Bao; Yang Ke; Yifan Wang; Weiwei Wang; Yuehua Li; Yan Wang; Xiang Kui; Qixin Zhou; Han Zhou; Cheng Zhang; Dongming Zhou; Lin Wang; et al. (Journal of Molecular Medicine, 2018)

Mitochondrial and nuclear genetic structure in Rhodeus ocellatus (Teleostei: Cyprinidae) with approximate Bayesian computation - Jin-Quan Yang; Kui-Ching Hsu; Po-Hsun Kuo; Lin-Lin Li; Wen-Qiao Tang; Dong Liu; Hung-Du Lin (Environmental Biology of Fishes, 2018)

Joint Interpretation of Geological, Magnetic, AMT, and ERT Data for Mineral Exploration in the Northeast of Inner Mongolia, China - Gang Zhang; Qing-Tian Lü; Gui-Bin Zhang; Ping-Rong Lin; Zheng-Yuan Jia; Kui Suo (Pure and Applied Geophysics, 2018)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

In vitro and in vivo studies of nematophagous fungi Arthrobotrys musiformis and Arthrobotrys robusta against the larvae of the trichostrongylides - Kui Zheng Cai; Bo Bo Wang; Qiang Xu; Jun Lin Liu; Kang Ying Wang; Yu Jia Xue; Hai Yan Zhang; Hai Yu Wang; Xin Cao; Zhong Ren Ma (Acta Parasitologica, 2017)
Six isolates of

Identification and characterization of differentially expressed miRNAs between bamboo shoot and rhizome shoot - Qun-Ying Jin; Hua-Zheng Peng; Er-Pei Lin; Nan Li; Dan-Ni Huang; Yan-Li Xu; Xi-Qi Hua; Kui-Hong Wang; Tang-Jun Zhu (Journal of Plant Biology, 2016)

Different evolutionary patterns of SNPs between domains and unassigned regions in human protein-coding sequences - Erli Pang; Xiaomei Wu; Kui Lin (Molecular Genetics and Genomics, 2016)

Two new eudesmane-type glucopyranosides from the fruits of Daucus carota L. - Jin-Ke Xu; Xiang-Hong Lu; Wei Zhu; Bing-Xian Yang; Lin Zhang; Jing-Kui Tian (Natural Product Research, 2015)

Effect of input pathways and altitudes on spatial distribution of polycyclic aromatic hydrocarbons in background soils, the Tibetan Plateau - Qiusheng He; Guixiang Zhang; Yulong Yan; Yiqiang Zhang; Laiguo Chen; Kui Lin (Environmental Science and Pollution Research, 2015)

Single nucleotide polymorphisms in PDCD6 gene are associated with the development of cervical squamous cell carcinoma - Bin Zhou; Peng Bai; Hui Xue; Zhu Zhang; Shaoqing Shi; Kui Zhang; Yanyun Wang; Kana Wang; Yi Quan; Yaping Song; Lin Zhang (Familial Cancer, 2015)

Molecular characterization of swine leukocyte antigen class I genes by sequence-based and PCR-SSP method in Guizhou minipigs - Jihan Xia; Zizhan Liu; Leilei Xin; Zaigui Wang; Lin Qian; Shuguang Wu; Shulin Yang; Kui Li (Molecular Biology Reports, 2014)

Differences in functional activity between boys with pure oppositional defiant disorder and controls during a response inhibition task: a preliminary study - Yan Zhu; Kui Ying; Ji Wang; Linyan Su; Jingyuan Chen; Fan Lin; Dongyang Cai; Ming Zhou; Daxing Wu; Courtney Guo; Shi Wang (Brain Imaging and Behavior, 2014)

A polymorphism at miRNA-122-binding site in the IL-1α 3′UTR is associated with risk of epithelial ovarian cancer - Zhu Zhang; Bin Zhou; Qianqian Gao; Yuke Wu; Kui Zhang; Yan Pu; Yaping Song; Lin Zhang; Mingrong Xi (Familial Cancer, 2014)

The study of regulatory effects of Pdx-1, MafA and NeuroD1 on the activity of porcine insulin promoter and the expression of human islet amyloid polypeptide - Xiao-Dan Liu; Jin-Xue Ruan; Ji-Han Xia; Shu-Lin Yang; Jun-Hua Fan; Kui Li (Molecular and Cellular Biochemistry, 2014)

Mitochondrial DNA phylogeography of Semisulcospira libertina (Gastropoda: Cerithioidea: Pleuroceridae): implications the history of landform changes in Taiwan - Kui-Ching Hsu; Hor Bor; Hung-Du Lin; Po-Hsun Kuo; Mian-Shin Tan; Yuh-Wen Chiu (Molecular Biology Reports, 2014)

Prognostic value of IL-27 polymorphisms and the susceptibility to epithelial ovarian cancer in a Chinese population - Zhu Zhang; Bin Zhou; Yuke Wu; Qianqian Gao; Kui Zhang; Yaping Song; Lin Zhang; Mingrong Xi (Immunogenetics, 2014)

A new indole alkaloidal glucoside from the aerial parts of Clematis terniflora DC. - Wen-Ting Li; Bing-Xian Yang; Wei Zhu; Ming-Hua Gong; Xiang-Dong Xu; Xiang-Hong Lu; Lian-Li Sun; Jing-Kui Tian; Lin Zhang (Natural Product Research, 2013)

The role of MrbHLH1 and MrMYB1 in regulating anthocyanin biosynthetic genes in tobacco and Chinese bayberry (Myrica rubra) during anthocyanin biosynthesis - Xiao-Fen Liu; Xue-Ren Yin; Andrew C. Allan; Kui Lin-Wang; Yan-Na Shi; Yu-Ji Huang; Ian B. Ferguson; Chang-Jie Xu; Kun-Song Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Transcriptional responses of maize seedling root to phosphorus starvation - Hai-Jian Lin; Jian Gao; Zhi-Ming Zhang; Ya-Ou Shen; Hai Lan; Li Liu; Kui Xiang; Maojun Zhao; Shufeng Zhou; Yong-Zhong Zhang; Shi-Bin Gao; Guang-Tang Pan (Molecular Biology Reports, 2013)

The prognostic value of MGMT promoter methylation in Glioblastoma multiforme: a meta-analysis - Kui Zhang; Xiao-qin Wang; Bin Zhou; Lin Zhang (Familial Cancer, 2013)

Al-enhanced Expression and Interaction of 14-3-3 Protein and Plasma Membrane H+-ATPase is Related to Al-induced Citrate Secretion in an Al-resistant Black Soybean - Chuan-Long Guo; Qi Chen; Xiu-Ling Zhao; Xuan-qian Chen; Yan Zhao; Lin Wang; Kui-Zhi Li; Yong-Xiong Yu; Li-Mei Chen (Plant Molecular Biology Reporter, 2013)

Different Gene Expressions of Resistant and Susceptible Maize Inbreds in Response to Fusarium verticillioides Infection - Guangsheng Yuan; Zhiming Zhang; Kui Xiang; Yaou Shen; Juan Du; Haijian Lin; Li Liu; Maojun Zhao; Guangtang Pan (Plant Molecular Biology Reporter, 2013)

Genetic diversity and evolutionary characterization of Chinese porcine reproductive and respiratory syndrome viruses based on NSP2 and ORF5 - Jian-Kui Liu; Chun-Hua Wei; Xiao-Yan Yang; Xi-Lin Hou; AI-Ling Dai; Xiao-Hua Li; Mei-Kang Wei; Xiu-Zhen Pan (Archives of Virology, 2013)

Halomonas socia sp. nov., isolated from high salt culture of Dunaliella salina - Jiao Cao; Huai-Yuan Ma; Hai-Yu Li; Kui-Rong Wang; Kun Ruan; Lin-Han Bai (Extremophiles, 2013)

Rural tourism development in China: Principles, models and the future - Ling-en Wang; Sheng-kui Cheng; Lin-sheng Zhong; Song-lin Mu; Bijaya G. C. Dhruba; Guo-zhu Ren (Journal of Mountain Science, 2013)

Mechano growth factor (MGF) promotes proliferation and inhibits differentiation of porcine satellite cells (PSCs) by down-regulation of key myogenic transcriptional factors - Li-Li Qin; Xiao-Kui Li; Jian Xu; De-Lin Mo; Xiong Tong; Zhi-Cheng Pan; Jia-Qi Li; Yao-Sheng Chen; Zhe Zhang; Chong Wang; Qiao-Ming Long (Molecular and Cellular Biochemistry, 2012)

The IL-10 promoter haplotype and cancer risk: evidence from a meta-analysis - Kui Zhang; Lushun Zhang; Xianmin Wang; Lin Zhang (Familial Cancer, 2012)

An updated meta-analysis of the p53 codon 72 polymorphism and gastric cancer risk - Kui-Jie Liu; Hai-Zhi Qi; Hong-Liang Yao; San-Lin Lei; Zhen-Dong Lei; Tie-Gang Li; Hua Zhao (Molecular Biology Reports, 2012)

Cloning and characterization of miRNAs from maize seedling roots under low phosphorus stress - Zhiming Zhang; Haijian Lin; Yaou Shen; Jian Gao; Kui Xiang; Li Liu; Haiping Ding; Guangsheng Yuan; Hai Lan; Shufeng Zhou; Maojun Zhao; Shibin Gao; et al. (Molecular Biology Reports, 2012)

Molecular Characteristics of the Porcine TIMD4 Gene and Its Association Analysis - Jing Yuan; Zhong-Lin Tang; Shulin Yang; Ji-Yue Cao; Kui Li (Biochemical Genetics, 2012)

Verrucosispora wenchangensis sp. nov., isolated from mangrove soil - Qing-yi Xie; Hai-peng Lin; Lei Li; Roselyn Brown; Michael Goodfellow; Zixin Deng; Kui Hong (Antonie van Leeuwenhoek, 2012)

Molecular characterization of Antarctic actinobacteria and screening for antimicrobial metabolite production - Learn-Han Lee; Yoke-Kqueen Cheah; Shiran Mohd Sidik; Nurul-Syakima Ab Mutalib; Yi-Li Tang; Hai-Peng Lin; Kui Hong (World Journal of Microbiology and Biotechnology, 2012)

Micromonospora haikouensis sp. nov., isolated from mangrove soil - Qing-yi Xie; Zhi Qu; Hai-peng Lin; Lei Li; Kui Hong (Antonie van Leeuwenhoek, 2012)

An Estimation of the Manganese Requirement for Broilers from 1 to 21 Days of Age - Sufen Li; Yuexia Lin; Lin Lu; Lin Xi; Zhiyue Wang; Shoufeng Hao; Liyang Zhang; Kui Li; Xugang Luo (Biological Trace Element Research, 2011)

Streptomyces shenzhenensis sp. nov., a novel actinomycete isolated from mangrove sediment - Huo Hu; Hai-Peng Lin; Qingyi Xie; Lei Li; Xin-Qiang Xie; Ming Sun; Kui Hong (Antonie van Leeuwenhoek, 2011)

QTL analysis and candidate gene mapping for skin and flesh color in sweet cherry fruit (Prunus avium L.) - Suneth S. Sooriyapathirana; Amjad Khan; Audrey M. Sebolt; Dechun Wang; Jill M. Bushakra; Kui Lin-Wang; Andrew C. Allan; Susan E. Gardiner; David Chagné; Amy F. Iezzoni (Tree Genetics & Genomes, 2010)

Coordinated regulation of anthocyanin biosynthesis in Chinese bayberry (Myrica rubra) fruit by a R2R3 MYB transcription factor - Shan-Shan Niu; Chang-Jie Xu; Wang-Shu Zhang; Bo Zhang; Xian Li; Kui Lin-Wang; Ian B. Ferguson; Andrew C. Allan; Kun-Song Chen (Planta, 2010)

A novel polymorphism of GDF5 gene and its association with body measurement traits in Bos taurus and Bos indicus breeds - Yong Feng Liu; Lin Sen Zan; Kui Li; Shuan Ping Zhao; Ya Ping Xin; Qing Lin; Wan Qiang Tian; Zhi Wei Wang (Molecular Biology Reports, 2010)

Phylogenetic analysis of Mycoplasma suis isolates based on 16S rRNA gene sequence in China - Rong-Qiong Zhou; Kui Nie; Han-Cheng Huang; Shi-jun Hu; Zuo-yong Zhou; Hong-Lin Luo (Veterinary Research Communications, 2009)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

A MYB transcription factor regulates anthocyanin biosynthesis in mangosteen (Garcinia mangostana L.) fruit during ripening - Yossapol Palapol; Saichol Ketsa; Kui Lin-Wang; Ian B. Ferguson; Andrew C. Allan (Planta, 2009)

Estimating Long-Term Changes in China’s Village Landscapes - Erle Christopher Ellis; Nagaraj Neerchal; Kui Peng; Hong Sheng Xiao; Hongqing Wang; Yan Zhuang; Shou Cheng Li; Jun Xi Wu; Jia Guo Jiao; Hua Ouyang; Xu Cheng; Lin Zhang Yang (Ecosystems, 2009)

Demographic trade‐offs in a neutral model explain death‐rate–abundance‐rank relationship - Kui Lin; Da-Yong Zhang; Fangliang He (Ecology, 2009)
The neutral theory of biodiversity has been criticized for its neglect of species differences. Yet it is much less heeded that S. P. Hubbell's definition of neutrality allows species to differ in their birth and death rates as long as they have an equal per capita fitness. Using the lottery model of competition we find that fitness equalization through birth–death trade‐offs can make species coexist longer than expected for demographically identical species, whereas the probability of monodominance for a species under zero‐sum neutral dynamics is equal to its initial relative abundance. Furthermore, if newly arising species in a community survive preferentially they are more likely to slip through the quagmire of rareness, thus creating a strong selective bias favoring their community membership. On the other hand, high‐mortality species, once having gained a footing in the community, are more likely to become abundant due to their compensatory high birth rates. This unexpected result explains why a positive association between species abundance and per capita death rate can be seen in tropical‐forest communities. An explicit incorporation of interspecific trade‐offs between birth and death into the neutral theory increases the theory's realism as well as its predictive power.

Genomic cloning, expression and recombinant protein purification of α and β subunits of the allophycocyanin gene (apc) from the cyanobacterium Anacystis nidulans UTEX 625 - Song Qin; Zhihong Tang; Fan Lin; Lanping Amy Sung; Cheng Kui Tseng (Journal of Applied Phycology, 2004)

Distribution characteristics of SOM and nitrogen on the eastern slope of Gongga Mountain - Wang Lin; Ou Yang Hua; Peng Kui; Tian Yuqiang; Zhang Feng (Journal of Geographical Sciences, 2004)

Coexistence of cryptic species - Da‐Yong Zhang; Kui Lin; Ilkka Hanski (Ecology Letters, 2004)
Recent discovery of cryptic species in fig‐pollinating wasps creates a puzzle for the ecological competition theory: how do two or more apparently identical species coexist? Conventional theory predicts that they should not. Chesson (Trends Ecol. Evol., 1991, 6 , 26–28) identified one exception which he considered unlikely to occur in reality: coexistence might be possible if appropriate social behaviour was discriminately directed towards conspecifics and heterospecifics. Here we present an example of the exception by showing that two identical species with local mate competition and population size‐dependent sex ratio adjustment may coexist. The new findings about fig‐pollinating wasps provide a putative example of unexpected coexistence of identical competitors via this mechanism.

Isolation and characterization of microsatellite loci in Acrossocheilus paradoxus (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Kui-Ching Hsu; Jiang-Ping Wang; Xiang-Lin Chen; Tzen-Yuh Chiang (Conservation Genetics, 2004)

Strand Compositional Asymmetries of Nuclear DNA in Eukaryotes - Deng K. Niu; Kui Lin; Da-Yong Zhang (Journal of Molecular Evolution, 2003)

Design of environmental decision support system and its application to water quality management - Zeng Fan-tang; Du Ling; Lin Kui; Shen Qian (Journal of Geographical Sciences, 2001)